Diagnóstico de três comunidades na Reserva de Desenvolvimento Sustentável Piagaçu Purus – Amazonas Central quanto ao potencial de uso de produtos não-madeireiros que ocorrem em capoeira - (:unkn) unknown (Universidade Federal do Amazonas, 2008)
The aim of this study was to evaluate the non-timber plant species with economic potential in barns, land of 15 to 30 years in three traditional communities of RDS Piagaçu Purus. The search arose from a need to know the potential non-timber in secondary vegetation in the Central Amazon. In areas of the Reserve located in the Amazon - Brazil, were established twelve plots (100x20 m) for sampling of individuals, DAP> 10 cm, each of the parcels were subdivided into five parts (20x20 meters), within each sub-plot, was established a parcel of 5x5 m for counting the species with DAP <5 cm. 1,182 individuals were recorded in the lifting of DAP and 981 individuals with higher DAP minor. The families most representative regarding diversity were Moraceae (18 spp.), Fabaceae (16 spp.) and Annonaceae (15 spp.), These barns are dominated by species of the genus Miconia DAP greater than or equal to 10 cm and Astrocaryum DAP less than or equal to 5 cm. In the density of seedlings and adults, seven species were the most abundant species. The survey was conducted from inventory, personal interviews for the residents of three communities and informal conversations. This analysis considered the potential for generating income of the forest, using non-timber products of greatest interest, and the generation of income of families. We need investments of the company targeted to ensure the maintenance of families in rural areas so that they do not alone with the costs of conservation of forest ecosystems. The methodology could be replicated in other units of conservation in the state of Amazonas and the Amazon as a whole
Keywords: Floresta Amazônica; Vegetação Secundária; Manejo de capoeiras; Exploração de madeira; CIÊNCIAS AGRÁRIAS: RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL